2011
DOI: 10.1016/j.ad.2010.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Aproximación al diagnóstico dermatopatológico de las lesiones figuradas

Abstract: Both clinical and pathologic findings must be considered when diagnosing figurate skin lesions, which are often seen in routine practice. Although a skin biopsy may sometimes be diagnostic, more often the information provided is nonspecific. In an attempt to offer an approach to diagnosing these dermatoses, we have classified annular lesions according to the presence of lymphocytic, neutrophilic-eosinophilic, or granulomatous infiltrates, and infiltrates containing plasma cells. Neoplastic annular lesions are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…The latest case involved a 4-year-old boy, described by Kunz et al Since 2000, when the first case of eosinophilic annular erythema was reported in an adult woman, no further cases involving children have been described. 1-4 Histopathology is quite characteristic, revealing a superficial, deep, perivascular, inflammatory infiltrate composed of lymphocytes and abundant eosinophils. ¨Flame figures¨ are unusual and were first described by Rongioletti et al in two out of four adult patients, and later by El-Khalawany et al in seven out of ten adult patients with well-developed, long-standing lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latest case involved a 4-year-old boy, described by Kunz et al Since 2000, when the first case of eosinophilic annular erythema was reported in an adult woman, no further cases involving children have been described. 1-4 Histopathology is quite characteristic, revealing a superficial, deep, perivascular, inflammatory infiltrate composed of lymphocytes and abundant eosinophils. ¨Flame figures¨ are unusual and were first described by Rongioletti et al in two out of four adult patients, and later by El-Khalawany et al in seven out of ten adult patients with well-developed, long-standing lesions.…”
Section: Discussionmentioning
confidence: 99%
“…¨Flame figures¨ are unusual and were first described by Rongioletti et al in two out of four adult patients, and later by El-Khalawany et al in seven out of ten adult patients with well-developed, long-standing lesions. 1-4 One important differential diagnosis is annular erythema in childhood, a rare entity that differs from eosinophilic annular erythema due to the presence of lesions that feature predominantly in children aged under 1, entailing spontaneous resolution and eosinophilic infiltration. 3 The main differential histopathological diagnosis is Wells' syndrome, also known as eosinophilic cellulitis, where tissue eosinophilia and the presence of "flame figures" are characteristic.…”
Section: Discussionmentioning
confidence: 99%
“…the interstitial granulomatous reaction that is most often due to antihypertensives or lipid-lowering agents but can also be associated with certain forms of autoimmune diseases. It is characterized by palisading granulomas surrounding small collagenous deposits [1].…”
Section: Discussionmentioning
confidence: 99%
“…In the histology of psoriasis, neutrophil infiltrates in epidermis and parakeratosis are typically observed. Ichthyosis linearis circumflexa in Netherton syndrome is associated with atopic diathesis, highly elevated serum IgE and its erythematous plaques are bordered by double-edged scales [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation